Hydrograph rise times: technical report - Kar, Songthara Om, author; Colorado State University, Civil Engineering Department, publisher (Colorado State University. Libraries, 1967)
The runoff distribution with respect to time is needed for the design of many hydraulic structures. In most of the presently available techniques of flood peak estimation and design hydrograph prediction, it is necessary to determine characteristic or critical hydrograph times. This study suggests the use of the hydrograph rise time, which is the time between the commencement of runoff and the maximum discharge measured at a stream gaging station, as the time characteristic of a particular watershed. It is shown, however, that rise times within a watershed have considerable variability but a general distribution of values may be applied to all the watersheds used in this study. Because of the inadequacy of the existing rise time prediction methods, several new equations are derived in a stepwise regression analysis by computer. The investigation uses 407 flood events of 47 watersheds in 13 states, which is a larger sample than the data in any previous study of the same type. The conclusions are limited to floods caused by thunderstorms or storms of short duration (two or three hours) which are generally the most critical for small watersheds. Different equations are obtained for estimating median rise times in humid regions and arid regions.
CER66-67SO33.
June 1967.
Prepared for Bureau of Land Management.
Keywords: Runoff -- Mathematical models; Water-supply -- Mathematical models; Hydraulic structures